The problem of determining the public-service activities of the national police - Vdovichen, Vitalii (Toronto, Canada: European Scientific Platform, 2020)
The introduction of the new term «provision of services» made it possible to take a significant step towards rethinking the role, tasks and purpose of the National Police, bringing its activities closer to European standards. This should help improve the response to all citizens' appeals, improve the performance of the public service function of the police by providing quality services to the population. In fact, this is exactly what Article 2 of the Law of Ukraine «About the National Police» indicates, in particular, the spheres of «provision of police services» proclaim the entire field of police activity: ensuring public safety and order; protection of human rights and freedoms, the interests of society and the state; crime prevention; provision of services to assist persons who, for personal, economic, social reasons or as a result of emergencies, need such assistance, within the limits set by law [3]. Thus, police services are not the end result of policing. They can be recognized as services only in terms of understanding it as a process of activity, or the inseparable unity of activity and the result consumed in the process of its creation. This approach to the definition of police service is confirmed by the need for systematic and continuous counteraction to crime and public safety. Therefore, it indicates the need to revise the approach chosen in the legislation in order to eliminate the contradictory perception of the elements of a single system of public services.
Keywords: administrative-legal status; police services; police